Usability Quality Model of Documents Circulation software - V. V. Bakhtizin; A. A. Vorvul (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Usability model of documents circulation software is suggested. This model is being applied for the usability quality estimation. The example of search, calculation and quality properties confirmation of the suggested usability model is shown.